2021
DOI: 10.3390/ijms22094523
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophanyl-tRNA Synthetase as a Potential Therapeutic Target

Abstract: Tryptophanyl-tRNA synthetase (WRS) is an essential enzyme that catalyzes the ligation of tryptophan (Trp) to its cognate tRNAtrp during translation via aminoacylation. Interestingly, WRS also plays physiopathological roles in diseases including sepsis, cancer, and autoimmune and brain diseases and has potential as a pharmacological target and therapeutic. However, WRS is still generally regarded simply as an enzyme that produces Trp in polypeptides; therefore, studies of the pharmacological effects, therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…Consistent with this notion, we found that MUC1-C is necessary for expression of immunosuppressive indoleamine-2,3-dioxygenase-1 (IDO1), tryptophanyl-tRNA synthetase (WARS, WRS) and PTGES effectors ( Figure 5b ). IRF1 induces (i) IDO1, which reduces tryptophan (Trp) levels in the TME that are necessary for T cell proliferation and function, 49 (ii) WARS that is associated with IDO1 expression and protects cancer cells from Trp depletion, 50 , 51 and (iii) PTGES, which is required for the synthesis of PGE2, an inhibitor of T cell function. 52 Analysis of the TCGA-PRAD and SU2C-CRPC datasets further demonstrated that MUC1-high PCs significantly associate with upregulation of IDO1 ( Figure 5c ; Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this notion, we found that MUC1-C is necessary for expression of immunosuppressive indoleamine-2,3-dioxygenase-1 (IDO1), tryptophanyl-tRNA synthetase (WARS, WRS) and PTGES effectors ( Figure 5b ). IRF1 induces (i) IDO1, which reduces tryptophan (Trp) levels in the TME that are necessary for T cell proliferation and function, 49 (ii) WARS that is associated with IDO1 expression and protects cancer cells from Trp depletion, 50 , 51 and (iii) PTGES, which is required for the synthesis of PGE2, an inhibitor of T cell function. 52 Analysis of the TCGA-PRAD and SU2C-CRPC datasets further demonstrated that MUC1-high PCs significantly associate with upregulation of IDO1 ( Figure 5c ; Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IRF1 is an essential regulator of downstream effectors, such as IDO1, 49 WARS 50 , 51 and PTGES, 52 that promote immunosuppression of the TME by metabolically inhibiting T cell functions. IRF1 also drives ISG15 56–58 and SERPINB9 59 , 60 that confer resistance of cancer cells to CTL killing.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting ROS arrests actin dynamics. Sepsis and septic shock are also characterized by increased neutrophil protease levels, i.e., neutrophil elastase, fibrin and matrix metalloproteinases, and MPO, which results in production of WARS [ 54 ]. Aromatic D-tryptophan and D-phenylalanine may elicit a chemotactic response via activation of HCAR3 and fMLP, suggesting their synergistic action on neutrophils [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its host gene, WARS, encodes the enzyme tryptophanyl-tRNA synthetase, which is known to catalyze the tryptophan-tRNA ligation, which is key for protein synthesis [ 54 ]. WARS has been previously studied for its role in the innate inflammatory response, where it was found to act via Toll-like receptor activation and regulate the immune cell response [ 54 , 55 , 56 ]. In the present study, we showed that circWARS harbored multiple binding sites for key β-cell miRNAs and RBPs, including Ago2.…”
Section: Discussionmentioning
confidence: 99%